Pain behavior in SCN9A (Nav1.7) and SCN10A (Nav1.8) mutant rodent models. (14th May 2021) - Xue, Yaping; Chidiac, Celeste; Herault, Yann; Gaveriaux-Ruff, Claire
Highlights: Rodent genetic models highlight the role of SCN9A /Nav1.7 and SCN10A /Nav1.8 voltage-gated sodium channels in pain control. Full Scn9a knockout (KO) animals display pain insensitivity similar to congenital insensitivity to pain patients. The conditional KO mouse lines allow the assignation of Scn9a expressed in different cell populations in pain control. Targeting Nav1.7 and Nav1.8 constitute potential therapies for pain. Abstract: The two voltage gated sodium channels Nav1.7 and Nav1.8 are expressed in the peripheral nervous system and involved in various pain conditions including inflammatory and neuropathic pain. Rodent models bearing deletions or mutations of the corresponding genes, Scn9a and Scn10a, were created in order to understand the role of these channels in the pathophysiological mechanism underlying pain symptoms. This review summarizes the pain behavior profiles reported in Scn9a and Scn10a rodent models. The complete loss-of-function or knockout (KO) of Scn9a or Scn10a and the conditional KO (cKO) of Scn9a in specific cell populations were shown to decrease sensitivity to various pain stimuli. The Possum mutant mice bearing a dominant hypermorphic mutation in Scn10a revealed higher sensitivity to noxious stimuli. Several gain-of-function mutations were identified in patients with painful small fiber neuropathy. Future knowledge obtained from preclinical models bearing these mutations will allow understanding how these mutations affect pain. In addition, the review gives perspectives for creating models that better mimic patients' pain symptoms in view to developing novel analgesic strategies.